Critical Assessment of Blockchain Applications in Zakat Literature: Lessons for Government and Future Directions - Arva Athallah Susanto (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
Blockchain technology is revolutionizing the financial sector, including zakat management within Islamic Social Finance (ISF). This study critically assesses blockchain’s potential to address zakat-related challenges, such as transparency, accountability, and efficiency. While blockchain's decentralized and secure nature offers promising solutions, its adoption remains limited due to obstacles like institutional readiness, public awareness, and regulatory issues. Using the PRISMA-based Systematic Literature Review (SLR) method, this study reviewed 22 documents from an initial 97 to evaluate the application of blockchain and other digital technologies such as AI and IoT in zakat management. These technologies provide new opportunities to improve zakat collection and distribution, but also face challenges in infrastructure and regulation, particularly in Muslim-majority countries. Governments play a key role in fostering the adoption of these technologies by aligning them with sharia compliance and creating supportive policies for digital transformation. This research contributes to the Islamic finance literature by offering insights into how blockchain and digitalization can enhance zakat's social impact. It also provides practical recommendations for policymakers to promote broader adoption of modern technologies in zakat management, helping optimize their effectiveness in poverty alleviation.